A Conceptual Framework on Design Strategies of Women’s Shelter for Domestic Violence Survivors in Fostering New Beginning of Life - Tan, Yanxian; Shari, Zalina (MAJ - Malaysia Architectural Journal, 2022)
Domestic violence remains a crucial public health issue in Malaysia amidst the Covid-19 pandemic. Recently, we have seen the rise of reported abused cases due to various social and financial factors that led to this cause. Shelters are a crucial form of support for the victims as they provide immediate protection to this vulnerable group. However, this essential service is inadequate, and there is no purpose-built facility for domestic violence survivors in Malaysia. In addition, there is a lack of research on built environment design guidelines of a fitted women’s shelter. Therefore, this study aims to formulate a conceptual framework of an ideal women’s shelter model for domestic violence survivors in fostering a new beginning of life. A qualitative method will be used to conduct interviews with the study group (domestic violence survivors and staff in women’s shelters) to obtain the responses that can be applied to this research. The results will explore the needs of the domestic violence survivors in women’s shelters to heal from the physical and psychological effects of violence with the integration of a healing environment and sense-sensitive design in the built environment. This study contributes to fortifying guidelines and design recommendations in designing a women’s shelter facility, especially to accommodate domestic violence survivors. Future research can further investigate more variables to the existing study on aspects that can enhance the well-being and livelihood of domestic violence survivors in women’s shelters.